Colchicum tulakii (Colchicaceae), a new species from central Macedonia, northeastern Greece. (28th June 2021) - Tsiftsis, Spyros; Giannakis, Thomas; Panajiotidis, Sampson; Eleftheriadou, Eleni; Theodoropoulos, Konstantinos
Abstract : Colchicum tulakii Th. Giannakis, S. Tsiftsis & E. Eleftheriadou (Colchicaceae), a distinct new species from central Macedonia, northeast Greece, is described. A description, diagnostic characters and taxonomic comments on the new species are given. It is compared with its closely related taxa C. haynaldii, C. autumnale, C. turcicum and C. confusum . Ecological information is provided and the geographical distribution of the new species is mapped. Its conservation status was assessed according to the latest IUCN criteria.